TINGKAT PENGETAHUAN, PERSEPSI, DAN SIKAP MASYARAKAT MUSLIM TERHADAP KEHALALAN OBAT DI KECAMATAN WARUNGGUNUNG KABUPATEN LEBAK TAHUN 2024 - Fajrin Noviyanto; Sofi Nurmay Stiani; Ade Apriliani; Ade Anwar; Endi Muchyar; Afifah Nur Shobah (Universitas Mathla’ul Anwar Banten, 2025)
Given the large number of drugs found in the community that are believed to contain non-halal ingredients and do not have halal certificates from the MUI, the topic of halal drugs is very important to discuss. The purpose of this study is to determine the level of knowledge, understanding, and public perception of the halalness of drugs in Warunggunung District and the factors that influence public knowledge, understanding, and perception of the halalness of drugs. In this study, a descriptive approach model (non-experimental) was used. Sampling was carried out on the population of Warunggunung District using the propability sampling method. Questionnaires were used to collect data. According to the results of the study, the level of knowledge about the halalness of drugs in Warunggunung District is very good, with a score of 80%, the perception of the population of Warunggunung District towards the halalness of drugs is very good with a score of 71%, the attitude of the people of Warunggunung District is very good in terms of the halalness of drugs with a score of 87%. Overall, the level of public knowledge, perception, and attitude in Warunggunung District is very good. The results of the bivariate analysis based on the Spearman rank test prove that there is no clear relationship between the level of knowledge and sociodemographic attributes, perceptions, and attitudes towards the halalness of drugs P value <0.05.